2010
DOI: 10.1007/s11664-010-1286-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Co:Sb Molar Ratio on Synthesis and Properties of Undoped CoSb3 Prepared via a Polyol Method

Abstract: Nanostructured CoSb 3 was prepared via a polyol method using different Co:Sb molar ratios in the reactant precursors. X-ray diffraction (XRD) and fieldemission scanning electron microscopy (FESEM) were used to characterize the prepared products. Thermoelectric properties of the samples were measured from room temperature to around 500°C. The electrical resistivity and Seebeck coefficient were found to increase with increasing Sb content in the reactant precursors. The sample with a reactant precursor Co:Sb mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…The process here is modified by the addition of another reducing agent, such as NaBH 4 , and this synthetic method has been shown to synthesize thermoelectric materials with particles on the nanoscale. Previously, versions of the polyol method have been utilized to produce other thermoelectric materials, such as Bi 2 Te 3 , PbTe, Bi 1.5 Sb 0.5 Te 3 , and CoSb 3 . …”
Section: Introductionmentioning
confidence: 99%
“…The process here is modified by the addition of another reducing agent, such as NaBH 4 , and this synthetic method has been shown to synthesize thermoelectric materials with particles on the nanoscale. Previously, versions of the polyol method have been utilized to produce other thermoelectric materials, such as Bi 2 Te 3 , PbTe, Bi 1.5 Sb 0.5 Te 3 , and CoSb 3 . …”
Section: Introductionmentioning
confidence: 99%
“…Comparing these values to the mass fractions of the second phase in the samples, it confirmed that with larger mass fraction of second phase, there was increased scattering of phonons. It was noted that these lattice thermal conductivity values made up about 50% of the total thermal conductivity, which was close to the values reported by other authors [70,163,164]. However, as the total thermal conductivity was on the high side, it seems like the absolute value of lattice thermal conductivity was quite high.…”
Section: Thermoelectric Properties Measurementssupporting
confidence: 87%